Gender parity versus equity in the 21st century: The Crisis of Modern Societies: The Crisis of Modern Societies - Villalón Alejo, Lucía; Geraldes Da Cunha Lopes, Teresa María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The position of women today is a recurrent and differentiating theme. One of the pillars of democratic renewal and the legitimacy of democratic law considers gender parity. However, theoretically it undermines the fundamental key to democracy: the principle of equality. Because this is the first and last architectural link of any demo-cratic structure, it requires a series of instruments and other established principles - such as freedom - to become the principle of Equity. We show how equity introduces a set of remedial measures that contribute to the realization of a fairer society.